2020
DOI: 10.1186/s12910-020-00469-3
|View full text |Cite
|
Sign up to set email alerts
|

Self-evaluated ethical competence of a practicing physiotherapist: a national study in Finland

Abstract: Background: Patients have the right to equal, respectful treatment. Nowadays, one third of patient complaints concern health care staff's behavior towards patients. Ethically safe care requires ethical competence, which has been addressed as a core competence in physiotherapy. It has been defined in terms of character strength, ethical awareness, moral judgment skills in decision-making, and willingness to do good. The purpose of this study was to analyze the ethical competence of practicing physiotherapists. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…[42] In addition, it is recommended that PV education is delivered with more effective methods, because this reflects positively in patient care. [47] In this regard, the recent study of Kulju et al [19] showed that most of the physical therapists evaluated themselves highly ethically competent in all areas of ethical competence, subscales being strength, awareness, skills, and will. Willingness to do good was evaluated as highest, while character strength, including the strength to support ethical processes and speak on behalf of the patient, was evaluated the lowest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[42] In addition, it is recommended that PV education is delivered with more effective methods, because this reflects positively in patient care. [47] In this regard, the recent study of Kulju et al [19] showed that most of the physical therapists evaluated themselves highly ethically competent in all areas of ethical competence, subscales being strength, awareness, skills, and will. Willingness to do good was evaluated as highest, while character strength, including the strength to support ethical processes and speak on behalf of the patient, was evaluated the lowest.…”
Section: Discussionmentioning
confidence: 99%
“…[7] Therefore, during the last decades, normative descriptions of professional ethics have been published [8] and the body of literature examining physical therapy ethics has also increased. [5,[9][10][11][12][13][14][15][16][17][18][19] In this line, ethics has been defined as a set of values and a skill that can be learned and enhanced through professional practice. [20] Therefore, health professionals must have values related to their profession to detect ethical issues and guide decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…Our programme incremented also participants’ ethical competence. According to Guevara-Lòpez [ 37 ], ethical competencies are central elements for the development of palliative care, especially concerning truth-telling, which implies bidirectional trust between patients and healthcare providers [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since physiotherapists encounter a variety of ethical challenges in their practice, ethical competence is needed to respond to those challenges [24]. Physiotherapists consider themselves competent in ethics, even if they are not very familiar with ethical codes or methods for ethical problem-solving [24].…”
Section: Introductionmentioning
confidence: 99%
“…Since physiotherapists encounter a variety of ethical challenges in their practice, ethical competence is needed to respond to those challenges [24]. Physiotherapists consider themselves competent in ethics, even if they are not very familiar with ethical codes or methods for ethical problem-solving [24]. Previous training in ES could help to develop ethical competence and to face these situations in the most suitable way, providing highquality healthcare [17,18].…”
Section: Introductionmentioning
confidence: 99%